Ileal follicular lymphoma with atypical endoscopic findings - Yamada, Satoshi; Koshikawa, Yorimitsu; Minami, Naoki; Honzawa, Yusuke; Matsuura, Minoru; Nakase, Hiroshi (Endoscopy International Open, 2016)
A 72-year-old woman presented with symptomatic anemia without abdominal symptoms. She had no history of abdominal surgery or use of non-steroidal anti-inflammatory drugs. Enhanced computed tomography of the abdomen revealed swelling of multiple intraperitoneal lymph nodes and a high density of mesenteric adipose tissue. Fluorodeoxyglucose (FDG-) positron emission tomography showed high FDG accumulation at the intraperitoneal lymph nodes. Double-balloon enteroscopy detected severe stenosis with an annular ulcer in the lower ileum. She was diagnosed with ileal follicular lymphoma based on histologic examination and fluorescence in situ hybridization analysis of the biopsy specimen. The ileal ulcer was successfully treated by chemotherapy with rituximab and bendamustine for 1 year. We strongly recommend consideration of gastrointestinal follicular lymphoma in the differential diagnosis of annular ulcers in the small intestine.